Synthesis of organotellurium compounds by transmetalltion reaction of organomercury compounds / review - Asmaa B. Sabti; Hala Sabry Al-Ttbi; Khawla Sabeeh Brgaal (Genius Journals, 2022)
Synthetic organotellurium compounds have increased markedly recently as a result of their important applications in different fields, including synthetic intermediates, reagents, antioxidant agents, catalysts, antitumors, pharmaceutical agents, and organic synthesis, because the organotellurium group easily undergoes electrophilic or nucleophilic reactions. There are a variety of synthetic routes to prepare organotellurium compounds. In this review, we will discuss the method of preparing organic tellurium compounds using the transmetallation reaction of organomercury compounds. Using this method, many organic tellurium compounds based on amines, pyrazole, shiff base, azo, and thiadiazole moiety were prepared, which may not be prepared by other methods
Keywords: compounds; organotellurium; electrophilic; preparing